Swallowing disorders after thyroidectomy: What we know and where we are. A systematic review. (May 2017) - Scerrino, Gregorio; Tudisca, Chiara; Bonventre, Sebastiano; Raspanti, Cristina; Picone, Dario; Porrello, Calogero; Paladino, Nunzia Cinzia; Vernuccio, Federica; Cupido, Francesco; Cocorullo, Gianfranco; Lo Re, Giuseppe; Gulotta, Gaspare
Abstract: Introduction: Dysphagia and hoarseness are possible complications that can be observed in patients undergoing thyroidectomy or other neck surgery procedures. These complaints are usually related to superior and inferior laryngeal nerves dysfunction, but these can appear even after uncomplicated surgical procedure. Methods: We reviewed the current literature available on MEDLINE database, concerning the swallowing disorders appearing after the thyroidectomy. The articles included in the review reported pathophysiology and diagnostic concerns. Results: Twenty articles were selected for inclusion in the review. Depends on the possible causes of the difficulty swallowing (related to nerve damage or appearing after uncomplicated thyroidectomy), different types of diagnostic procedures could be used to study patient discomfort, as well as intraoperative nerve monitoring, fiber optic laryngoscopy, endoscopy, pH monitoring, esophageal manometry and videofluorography. Among all these procedures, videofluorography is considered the gold standard to evaluate the entire swallowing process, since that allows a real-time study of all the three phases of swallowing: oral phase, pharyngeal phase and esophageal phase. Conclusion: The diagnostic procedures described can help to identify the mechanisms involved in swallowing disorders, with the aim to choose the best therapeutic option. More studies are needed for understanding the causes of the dysphagia appearing after thyroidectomy. Highlights: Dysphagia and hoarseness can be observed in patients that underwent thyroidectomy. The current literature available on MEDLINE database, concerning the swallowing disorders appearing after the thyroidectomy was reviewed. Different diagnostic procedures could be used to study patient discomfort, as well as intraoperative nerve monitoring, fiber optic laryngoscopy, endoscopy, pH monitoring, esophageal manometry and videofluorography. The diagnostic procedures described can help to identify the mechanisms involved in swallowing disorders. More studies are needed for understanding the causes of the dysphagia appearing after thyroidectomy.